Some enzymatic properties of lactic acid bacteria isolated from dairy products - Admanova, G.B.; Kuanbay, Zh.I.; Izimova, R.; Keubassova, G.O.; Kozhamzharova, L.S. (Fundamental and Experimental Biology, 2023)
This article presents data on the study of physiological and biochemical properties, antagonistic and enzymatic activity of lactic acid bacteria isolated from dairy products.9 types of lactic acid bacteria were studied:Lactobacillus bulgaricus GM – 08, Lactobacillus bulgaricus KZh – 01,Lactobacillus bulgaricus GS – 03, Lactococcus cremoris – 6, Lactococcus cremoris – 17, Lactococcus cremoris – 26, Lactococcus lactis – 1,Lactococcus lactis – 15, Lactococcus lactis – 23. These strains were found to have resistance to 2% and 4%-vertical NaCl concentrations, bile and phenol.In addition, the antagonistic activity of Gram-positive and Gram-negative microorganisms in relation to test cultures of Staphylococcus aureus, Salmonella dublin, Escherichia coli, Bacillus subtilis, Sarcina flava was studied.All studied lactic acid bacteria showed activity in Test cultures with different inhibition zones. The Lactococcus lactis – 23 strains showed high activity for all cultures, with an inhibition zone of 17-25 mm.Further, 5 strains were selected from these strains and their aroma-forming properties, the formation of diacetyl and ammonia from arginine, hemolytic and lecithinase activity were studied.Compositions were compiled from these strains to make yeast.The compatibility of strains of lactic acid bacteria was checked with each strain individually and with the duration of milk clotting according to organoleptic indicators compared to the duration of milk clotting.Thus, the most active clot formation was obtained by the Lactococcus lactis – 23 strainof the selected combinations.